Growth of Ethnic Groups in Forest Villages of Buxa Tiger Reserve, West Bengal - Das, Bidhan Kanti (Indian Forester, 2005)
During the policy of 'commercial forestry', forest authorities allowed people of diverse ethnic groups to stay within Buxa forest to utilize their skills in clear felling coupes (CFC) and regeneration of plantations as well as other forestry activities. As a result, various forest villages formed in and around Buxa forest since 1894. This study attempts to identify ethnic groups and their concentration in each village as well as to assess the extent of population growth and consequent landholding status in each village. The study reveals that the Nepali community is the most dominant ethnic group in forest villages of BTR. Rava community comes next. It is also observed that average number of household has increased tremendously as compared to number of households before 1970. High population growth might be due to high fertility, low status of women, migration, lack of awareness about family planning, low literacy level especially among women. It obviously leads to landlessness, reduction of average land holding status as well as per capita land holding. It is felt that population control might be one of the major option to reduce pressure on forest wealth of BTR in future.